2021
DOI: 10.1080/23311932.2020.1855818
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Design and Constraints of Physical Soil and Water Conservation Structures in respect to the standard in the case of Gidabo sub-basin, Ethiopia

Abstract: In Ethiopia modern soil and water conservation (SWC) started in the 1970s. Due to several factors, most SWC works have not fully achieved the intended objectives. The disparity between dimensions of the implemented SWC work and the standard is the main factor. Therefore, this research work aimed to assess the design and constraints of SWC in the Gidabo sub-basin, of the Ethiopian rift valley. Data were generated through field observation, field measurements, household survey, interview, group discussion, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The farmers said that the implementation of SWC work without the application of chemical fertilizers was meaningless. This result agrees with the study report by [31] in the Gidabo watershed of southeastern Ethiopia.…”
Section: F Constraints To Adopt and Adapt The Soil And Water Conservation Practicessupporting
confidence: 93%
“…The farmers said that the implementation of SWC work without the application of chemical fertilizers was meaningless. This result agrees with the study report by [31] in the Gidabo watershed of southeastern Ethiopia.…”
Section: F Constraints To Adopt and Adapt The Soil And Water Conservation Practicessupporting
confidence: 93%
“…These areas are characterized by lower tree cover, unsustainable land management practices, accelerated carbon decomposition and erosion. In line with this, Degefa [80], Debelo et al [81] and Hassen et al [82] indicated that trend in agricultural productivity has declined over the last decades given that climate change, soil erosion, and poor soil and water conservation (SWC) practices were mentioned as the main drivers. This, in turn, resulted in increased demand for farm inputs (e.g., fertilizer, pesticides) and increased production costs.…”
Section: Land Degradation Pathwaysmentioning
confidence: 89%
“…The Gidabo Watershed is part of Rift Valley Basin, and also called Ethiopian Rift runs through Ethiopia in the southwest direction from the Afar Triple Junction (Elias et al, 2019). This area is characterized by wide topography and climatic variation ranging from humid in the highland to semi-arid (Hassen et al, 2021). It is situated between 6 0 9' 4'' to 6 0 56' 4''N latitude and 37 0 55' to 38 0 35''E longitude, covering an area that is approximately 3549 km 2 (Figure 1).…”
Section: Description Of Research Sitesmentioning
confidence: 99%